Future Representation of Species’ Climatic Niches in Protected Areas: A Case Study With Austrian Endemics - Semenchuk, Philipp; Moser, Dietmar; Essl, Franz; Schindler, Stefan; Wessely, Johannes; Gattringer, Andreas; Dullinger, Stefan (Frontiers in Ecology and Evolution, 2021)
Climate driven species’ range shifts may interfere with existing protected area (PA) networks, resulting in a mismatch between places where species are currently protected and places where they can thrive in the future. Here, we assess the climate-smartness of the Austrian PA network by focusing on endemic species’ climatic niches and their future representation within PAs. We calculated endemic species’ climatic niches and climate space available in PAs within their dispersal reach under current and future climates, with the latter represented by three climate change scenarios and three time-steps (2030, 2050, and 2080). Niches were derived from the area of occupancy of species and the extent of PAs, respectively, and calculated as bivariate density kernels on gradients of mean annual temperature and annual precipitation. We then computed climatic representation of species’ niches in PAs as the proportion of the species’ kernel covered by the PA kernel. We found that under both a medium (RCP 4.5) and severe (RCP 8.5) climate change scenario, representation of endemic species’ climatic niches by PAs will decrease to a sixth for animals and to a third for plants, on average, toward the end of the century. Twenty to thirty percent of Austrian endemic species will then have no representation of their climatic niches in PAs anymore. Species with larger geographical and wider elevational ranges will lose less climatic niche representation. The declining representation of climatic niches in PAs implies that, even if PAs may secure the persistence of a part of these endemics, only a small portion of intraspecific diversity of many species may be represented in PAs in the future. We discuss our findings in the context of the varied elevational gradients found in Austria and suggest that the most promising strategies for safeguarding endemic species’ evolutionary potential are to limit the magnitude of climate change and to reduce other pressures that additionally threaten their survival.